Estimation of the Postmortem Interval by Measuring Blood Oxidation-reduction Potential Values - Zhuqing Jiang; Meng You; Xu Wang; Di Lu; Haidong Zhang; Shengli Di; Fengqin Zhang; Zhaoming Guo; Xiaofei E; Lin Chang; Jian Xiang; Rufeng Bai; et al. (Wolters Kluwer Medknow Publications, 2016)
Accurate estimation of the postmortem interval (PMI) is an important task in forensic practice. In the last half-century, the use of postmortem biochemistry has become an important ancillary method in determining the time of death. The present study was carried out to determine the correlation between blood oxidation-reduction potential (ORP) values and PMIs, and to develop a three-dimensional surface equation to estimate the PMI under various temperature conditions. A total of 48 rabbits were placed into six groups and sacrificed by air embolism. Blood was obtained from the right ventricle of each rabbit, and specimens were stored at 10°C, 15°C, 20°C, 25°C, 30°C, and 35°C. At different PMIs (once every 4 h), the blood ORP values were measured using a PB-21 electrochemical analyzer. Statistical analysis and curve fitting of the data yielded cubic polynomial regression equations and a surface equation at different temperatures. Result: The results showed that there was a strong positive correlation between the blood ORP values at different temperatures and the PMI. This study provides another example of using a three-dimensional surface equation as a tool to estimate the PMI at various temperature conditions.